A Confirmatory Factor Analysis of a Newly Integrated Multidimensional School Engagement Scale (Malaysian Journal of Learning and Instruction, 2008)
Inconsistencies in measures of school engagement in the literature have called for a re-conceptualization of the school engagement construct. Although many researchers view school engagement as a multifaceted construct, to our knowledge, none of the available instruments have integrated all the important domains that represent its multifaceted nature. This study is our first attempt to examine the psychometric properties of a newly integrated Multidimensional School Engagement Scale (MSES). Data were gathered from 2,381 secondary school students, aged 14 to 16, from 40 day schools in northern Malaysia. Exploratory factor analysis and confirmatory factor analytic techniques were used to examine the instrument. Based on the available literature, we posited an a priori hypothesis that the scales could be explained by three first-order factors and one second-order factor. We used SPSS v.12 and AMOS 6.0 to analyze the data. Findings supported our hypothesis that the school engagement construct can be explained by three first-order factors and one hierarchical factor comprising cognitive engagement, behavioural engagement, and psychological engagement sub-scales. Findings also showed acceptable internal consistency reliability for the overall scale and the three specific sub-scales of adolescent school engagement.